2015
DOI: 10.3389/fpls.2015.01086
|View full text |Cite
|
Sign up to set email alerts
|

De novo Transcriptome Assembly of a Chinese Locoweed (Oxytropis ochrocephala) Species Provides Insights into Genes Associated with Drought, Salinity, and Cold Tolerance

Abstract: Background: Locoweeds (toxic Oxytropis and Astraglus species), containing the toxic agent swainsonine, pose serious threats to animal husbandry on grasslands in both China and the US. Some locoweeds have evolved adaptations in order to resist various stress conditions such as drought, salt and cold. As a result they replace other plants in their communities and become an ecological problem. Currently very limited genetic information of locoweeds is available and this hinders our understanding in the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…Generally, TFs can regulate the downstream genes involved in responses to environment stress, e.g., MYB, NAC, WRKY and ERF etc. [ 29 , 44 ]. These TFs have been proven to be significantly associated with various environment stresses in many plants [ 36 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, TFs can regulate the downstream genes involved in responses to environment stress, e.g., MYB, NAC, WRKY and ERF etc. [ 29 , 44 ]. These TFs have been proven to be significantly associated with various environment stresses in many plants [ 36 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Banzet et al [ 43 ] reported that HSP22 can protect plant cells against oxidative injury. He et al [ 44 ] found the class I heat shock protein 18.2 is down-regulated by a cold treatment but did not show significant differential expression. In addition, small heat shock proteins are very stable, which may be helpful for self-repair mechanisms in plants following exposure to abiotic stresses [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining clean reads were assembled using Trinity software with default parameters [ 40 , 41 ]. Generally, three steps were performed, including Inchworm, Chrysalis and Butterfly [ 42 ]. In the first step, clean reads were operated by Inchworm to form longer fragments, called contigs.…”
Section: Methodsmentioning
confidence: 99%